High-performing natural materials (Leonurus cardiaca): dye biosorption studies and statistical analysis - Akdemir, Melike; Isik, Birol; Cakar, Fatih; Cankurtaran, Ozlem (SPRINGER HEIDELBERG, 2023)
Lignocellulosic materials have been widely used in recent years for the sorption of different contaminants from wastewater because of high adsorption capacity, zero waste, low cost, and sustainability. In this study, a lignocellulosic adsorbent, Leonurus cardiaca leaf, and stem were used to remove Basic Red 2 (BR2) from wastewater. By using FTIR-ATR, SEM, TGA, BET, pH(pzc), and zeta potential studies, adsorbents were characterized. From the BET experiment, the surface areas of Leonurus cardiaca leaf and stem were calculated as 9.843 and 143.670 m(2)/g, respectively. It was discovered that adsorption occurred on monolayer and homogenous surfaces in accordance with the Langmuir isotherm after applying experimental data to various isotherms, including Freundlich, D-R, and Temkin. According to Langmuir isotherm, q(m) values for Leonurus cardiaca leaf and stem at 298 K were determined as 500.0 and 714.3 mg/g, respectively. The PSO model of adsorption was found to be followed, and it was also discovered that the adsorption process was chemical in nature based on the kinetics. Also, by applying the raw data to various error functions, the long-term viability of the adsorption process was assessed. From thermodynamic parameters, adsorption for adsorbents was found to be endothermic (23.7 kJ/mol for leaf and 2.3 kJ/mol for stem) and spontaneous (- 31.0 kJ/mol for leaf and - 28.5 kJ/mol for stem) at 298 K. All of the findings demonstrated that the leaf and stem of Leonurus cardiaca can be used as an efficient and eco-friendly adsorbent for the removal of cationic textile dyes from wastewater.
Keywords: Biosorption; Lignocellulosic material; Synthetic dye; Statistical analysis; ACTIVATED CARBON ISOTHERM; ADSORPTIVE REMOVAL; AQUEOUS-SOLUTIONS; CATIONIC DYES; KINETICS; EQUILIBRIUM; MECHANISM; ACID; Energy & Fuels; Engineering